2007
DOI: 10.3174/ajnr.a0546
|View full text |Cite
|
Sign up to set email alerts
|

Changes in T2 Relaxation Times Associated with Maturation of the Human Intervertebral Disk

Abstract: BACKGROUND AND PURPOSE: By calculating T2 relaxation times for intervertebral disks, we tested the hypothesis that disk water concentration increases between the first and second decades of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
1
9
2
Order By: Relevance
“…In the present study, the mean T2 values in normal cervical discs was lower than those previously reported in healthy lumbar discs [15], [17], [22], [37]. This difference may due to the different biochemical properties characteristic of cervical and lumbar IVDs.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In the present study, the mean T2 values in normal cervical discs was lower than those previously reported in healthy lumbar discs [15], [17], [22], [37]. This difference may due to the different biochemical properties characteristic of cervical and lumbar IVDs.…”
Section: Discussioncontrasting
confidence: 87%
“…Several studies have described the benefits of T2 mapping as a technique for biochemical and structural analysis of cartilage tissue of the spine, IVD and other joints [12][14]. Good correlation between T2 mapping values and water or PG content in lumbar IVD tissue has widely validated [15][19]. Increased disc water or glycosaminoglycan content, the primary component of PG, is associated with increased T2, whereas increased collagen content contributes to decreased T2 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings suggested that ADC measurements may more sensitive in detecting early degenerative changes of IVDs. However, other studies have found the opposite [5], [20], [21], [22]. In our study, both ADC and T2 mean values were negatively correlated with age.…”
Section: Discussioncontrasting
confidence: 51%
“…14 Moreover, disk T2 varies with age, 18 magnitude, or duration of compression 21 and diurnal variation. 19 Therefore, T2 may serve as a potential quantitative and sensitive biomarker for detecting the IVDD at an early stage.…”
mentioning
confidence: 99%